Exploring quality indicators for the detection of -naïve gastric cancer: a cross-sectional nationwide survey - Fumiaki Ishibashi; Toshiaki Hirasawa; Hiroya Ueyama; Yohei Minato; Sho Suzuki (Korean Society of Gastrointestinal Endoscopy, 2023)
Background/Aims Diagnosis of Helicobacter pylori-naïve gastric cancer (HPNGC) is becoming increasingly important. This study aimed to explore the quality indicators for HPNGC detection. Methods We conducted a cross-sectional, nationwide, web-based survey of gastrointestinal endoscopists in Japan. In addition to questions about the number of HPNGC cases detected in a year and basic information, the questionnaire also consisted of 28 questions: (1) 18 about HPNGC awareness, (2) six about diagnostic proactiveness, and (3) four about interest in HPNGC. Results Valid responses were obtained from 712 endoscopists. The Japan Gastroenterological Endoscopy Society-certified endoscopists had a significantly higher HPNGC detection rate than the nonspecialists (0.42% vs. 0.32%, respectively; p=0.008). The results of the multiple regression analysis showed that Japan Gastroenterological Endoscopy Society certification and high awareness and interest scores were independent predictors of the HPNGC detection rate (p=0.012, p<0.001, p=0.024, respectively). Principal component analysis showed that the endoscopists who attended conferences for collecting information on HPNGC had a higher level of awareness. Conclusions To improve the detection of HPNGC, it is necessary to increase the awareness of the disease. It is hoped that relevant societies will play an important role in endoscopists' education.